Prey‐baiting as a conservation tool: selective control of invasive ants with minimal non‐target effects. Issue 4 (20th April 2017) - Buczkowski, Grzegorz
Abstract: Invasive ants are considered a significant threat to urban, agricultural, and natural habitats worldwide and the control of invasions is often a priority for conservation management. The spread and impact of invasive ants is often controlled using chemical management tools, predominantly toxic baits. The preferred outcome of such interventions is the recovery of indigenous species following the removal of the alien invader. Nonetheless, management actions may have unintended consequences such as non‐target impacts. Non‐target impacts are often a significant concern in areawide eradication programs because toxic baits are typically attractive to a wide range of animals and may kill non‐target fauna, especially other invertebrates. Development of effective techniques to control populations of invasive ants while protecting the non‐target fauna is important for conservation of native biodiversity. This study utilised laboratory and field experiments to evaluate a novel approach for managing invasive Asian needle ants ( Brachyponera chinensis ) utilising live, insecticide‐treated termite prey. The goal was to examine the potential ecological impact of toxic prey‐baiting on native ant fauna and to determine if toxic prey‐baiting is adequately selective to be used as a tool for eradicating Asian needle ants while preserving native ant communities. Protein marking was used to track the consumption of termite prey by target and non‐target ant species. Results demonstrate that prey‐baiting using live, fipronil‐treated termites is highly effective against Asian needle ants. Furthermore, prey‐baiting is highly specific with detrimental effects against the target species and negligible effects on native ants. Results demonstrate a novel management tool for conservation agencies working to eradicate invasive ants globally. While traditional bait treatments are typically non‐selective and eradicate a wide range of non‐targets, prey‐baiting is highly effective and target specific and may offer an effective alternative to traditional bait treatments. Additionally, prey‐baiting may provide environmental benefits with regard to pesticide residues in ecologically sensitive environments and other protected landscapes where invasive ants pose a threat to native organisms and must be carefully managed to avoid non‐target effects.